2010
DOI: 10.1080/10410231003698952
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Openness: Developing and Validating a Measure of Targeted Parent–Child Communication About Alcohol

Abstract: Research addressing parent-child communication on the topic of alcohol use relies heavily on assessing frequency of discussions and general assessments of openness in parent-child communication, ignoring the complexity of this communication phenomenon. This study adds to the literature by articulating a conceptualization and developing a measurement of parent-child communication-targeted parent-child communication about alcohol-and comparing the efficacy of targeted parent-child communication about alcohol in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 39 publications
5
142
2
2
Order By: Relevance
“…For example, a number of studies have found that effective parental monitoring of adolescent activities can reduce risk for substance use (Fosco, Stormshak, Dishion, & Winter, 2012;Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Van Ryzin, Fosco, & Dishion, 2012). Research also supports a link between parent-adolescent relationship quality and adolescent substance use (Hummel, Shelton, Heron, Moore, & Bree, 2013;Ledoux, Miller, Choquet, & Plant, 2002;Van Ryzin et al, 2012), as well as effective parent-youth communication and adolescent substance use (Kam, Basinger, & Abendschein, 2015;Kam, Castro, & Wang, 2015;Kam & Middleton, 2013;Miller-Day & Dodd, 2004;Miller-Day & Kam, 2010;Reimuller, Hussong, & Ennett, 2011;Zaharakis, Taylor, & Kliewer, 2015).…”
Section: Family Communication and Substance Use Preventionmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, a number of studies have found that effective parental monitoring of adolescent activities can reduce risk for substance use (Fosco, Stormshak, Dishion, & Winter, 2012;Griffin, Botvin, Scheier, Diaz, & Miller, 2000;Van Ryzin, Fosco, & Dishion, 2012). Research also supports a link between parent-adolescent relationship quality and adolescent substance use (Hummel, Shelton, Heron, Moore, & Bree, 2013;Ledoux, Miller, Choquet, & Plant, 2002;Van Ryzin et al, 2012), as well as effective parent-youth communication and adolescent substance use (Kam, Basinger, & Abendschein, 2015;Kam, Castro, & Wang, 2015;Kam & Middleton, 2013;Miller-Day & Dodd, 2004;Miller-Day & Kam, 2010;Reimuller, Hussong, & Ennett, 2011;Zaharakis, Taylor, & Kliewer, 2015).…”
Section: Family Communication and Substance Use Preventionmentioning
confidence: 94%
“…Past research (e.g., Kafka & London, 1991) has primarily focused on: (a) general openness or frequency of parent-child communication in relation to adolescent substance use, and more recently, (b) how SSPC relates to adolescent substance use (Kam & Middleton, 2013;Miller-Day & Kam, 2010). To extend such research, Choi and colleagues suggested that the effects of SSPC on adolescent substance use likely depend on their family communication environment, as characterized by their expressiveness, structural traditionalism, and avoidance.…”
Section: A Preview Of This Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…The Targeted Parent-Child Communication about Alcohol Scale (TPCCAS) 123 measures general openness, frequency and, specifically, alcohol-related content of parent-child communication. Development of the measure was based on evidence that parent-child communication which was more protective against substance misuse not only involved open and frequent general communication but also specifically addressed the topic of substance misuse.…”
mentioning
confidence: 99%